Formation and Evolution of the Corrosion Scales on Super 13Cr Stainless Steel in a Formate Completion Fluid With Aggressive Substances - Yue, Xiaoqi; Huang, Luyao; Qu, Zhihao; Yang, Zhile; Zhang, Lei; Hua, Yong (Frontiers in Materials, 2022)
The formation and evolution of the corrosion scales on the super 13Cr stainless steel (SS) surface after exposure in a formate completion fluid with the presence of various aggressive substances was investigated. The results indicate that the formation of Fe3O4 covered the surface of super 13Cr SS as the inner layer accompanied with outer scattered FeS. The corrosion rate was below 0.07 mm/year after 120 h of exposure in the formate fluid at 180°C under N2 environments; the presence of aggressive substances such as sulfide and CO2 in the formate fluid promoted the proceeding of anodic dissolution in the early period, and the ingress of CO2 progressively increased the general corrosion rate to 1.7 mm/year. For CO2-containing conditions, the formation of FeCr2O4 and Cr(OH)3 was detected in the inner corrosion product layers, and the precipitation of “sheet”-shaped iron carbonate (FeCO3) was detected as the outer layer. The accumulation rate of corrosion products increases by two orders of magnitude with the ingress of CO2, corresponding to thicker corrosion products, but the dissolution rate is still three orders of magnitude higher than when CO2 was absent.